Activation Cross Section Measurement of the (n,2n) Reaction on 203Tl - Patas, Stavros (HNPS Advances in Nuclear Physics, 2022)
The aim of the present work was to study the cross-section of the (n,2n) reaction on 203Tl, by irradiating a natural TlCl pellet target with monoenergetic neutron beam at 18.9 MeV. The cross section of the 203Tl(n,2n)202Tl reaction, was measured implementing the activation method, with respect to the 197Au(n,2n)196Au and 27Al(n,α)24Na reference reactions. The monoenergetic neutron beam was produced in the 5.5 MV Tandem accelerator of NCSR Demokritos, using the 3H(d,n)4He reaction. After the irradiation, the induced activity of the samples was measured with a HPGe detector, which was properly shielded with lead blocks to reduce the contribution of natural radioactivity. Monte Carlo simulations implementing the MCNP code have been performed to take into account the gamma-ray self-absorption results as well as the estimation of the neutron flux through the reference foils. Finally, a comparison of theoretical calculations with the code EMPIRE and experimental data was carried out, with the aim of finding a suitable model for the description of the reaction cross section under study.